Ethical Considerations in Psychoanalytic Writing Revisited. Issue 3 (1st September 2016) - Aron, Lewis
Abstract : The author updates a previous survey (Aron, 2000) of clinical and ethical concerns in the presentation and publication of case histories. Recent professional and social developments provide patients with greater access to psychoanalytic writing and increase the complexity involved in the decision to publish case material. The author presents a series of vignettes culled from professional experience and psychoanalytic history, illustrating potential pitfalls in the publication of case material with and without patient consent. Although asking for informed consent may risk alienating a patient, a series of cases demonstrate the ways in which patients perceive the request as collaborative or benefit from reading the publication. Editorial guidelines from mainstream psychoanalytic journals are compared and analyzed relative to those of the International Committee of Medical Journal Editors. Summarizing a range of opinions from most conservative to radical, the author advocates for an individualized approach. He concludes with a series of ethical, educational, legal, and clinical considerations applicable from beginning student to advanced psychoanalyst. The author advocates that therapists presenting and publishing extended case histories seek consultation before proceeding, as our case presentations should be regarded as forms of participation in meaningful clinical enactments. The author emphasizes the urgency for psychoanalytic educators to raise these questions and concerns with students from the start of their clinical education.